A novel proneural function of Asense is integrated with the sequential actions of Delta-Notch, L'sc and Su(H) to promote the neuroepithelial to neuroblast transition. - Martin, M.; Gutierrez-Avino, F.; Shaikh, M.N.; Tejedor, F.J. (PLoS Genetics, 2023)
In order for neural progenitors (NPs) to generate distinct populations of neurons at the right time and place during CNS development, they must switch from undergoing purely proliferative, self-renewing divisions to neurogenic, asymmetric divisions in a tightly regulated manner. In the developing Drosophila optic lobe, neuroepithelial (NE) cells of the outer proliferation center (OPC) are progressively transformed into neurogenic NPs called neuroblasts (NBs) in a medial to lateral proneural wave. The cells undergoing this transition express Lethal of Scute (L'sc), a proneural transcription factor (TF) of the Acheate Scute Complex (AS-C). Here we show that there is also a peak of expression of Asense (Ase), another AS-C TF, in the cells neighboring those with transient L'sc expression. These peak of Ase cells help to identify a new transitional stage as they have lost NE markers and L'sc, they receive a strong Notch signal and barely exhibit NB markers. This expression of Ase is necessary and sufficient to promote the NE to NB transition in a more robust and rapid manner than that of l'sc gain of function or Notch loss of function. Thus, to our knowledge, these data provide the first direct evidence of a proneural role for Ase in CNS neurogenesis. Strikingly, we found that strong Delta-Notch signaling at the lateral border of the NE triggers l'sc expression, which in turn induces ase expression in the adjacent cells through the activation of Delta-Notch signaling. These results reveal two novel non-conventional actions of Notch signaling in driving the expression of proneural factors, in contrast to the repression that Notch signaling exerts on them during classical lateral inhibition. Finally, Suppressor of Hairless (Su(H)), which seems to be upregulated late in the transitioning cells and in NBs, represses l'sc and ase, ensuring their expression is transient. Thus, our data identify a key proneural role of Ase that is integrated with the sequential activities of Delta-Notch signaling, L'sc, and Su(H), driving the progressive transformation of NE cells into NBs.